Efeito da incorporação da fibra de caju a um reestruturado proteico a base de pirarucu (Arapaima gigas) - Marques, Francisco Roberio da Silva (2018)
The industrial processing of fish and the cashew agro-industry generate large amounts of waste considered as raw materials for the production of co-products of high nutritional value. Thus, the use of by-products from different industries and the incentive to obtain differentiated products for human consumption motivated this research that had as objective to develop a restructured protein product in the form of a medallion based on pirarucu (Arapaima gigas) and cashew fiber (Anacardium occidentale L.) and to evaluate its physicochemical, microbiological properties and sensorial properties, as well as, the content of bioactive compounds incorporated into the product, observing a possible influence on the antioxidant activity and stability of the product during frozen storage. First, an affective sensory-preference-ordering test was performed to identify the best formulation of the medallions to be studied. In this test, it was identified that there was no significant difference (P> 0.05) between the formulations, so the medallion with 80% mechanically deboned meat (MDM) of pirarucu and 20% cashew fiber was chosen. Then, an acceptance test was performed to evaluate the attributes: color, flavor, aroma, texture, overall impression, as well as the intention to purchase the product. This study was carried out with both, the control formulation with 100% pirarucu MDM (MC) and a formulation with 20% cashew fiber (MF). In this analysis it was verified that for all evaluated attributes and for both formulations more than 50% of the notes were in the zone of acceptance of the hedonic scale. Regarding to purchase intent, more than 50% of the panellists revealed that they "would probably buy" and "certainly would buy" both formulations. The physicochemical stability of the medallions was evaluated through the following analyzes: pH, total volatile bases (N-TVB), trimethylamine (TMA), amount of thiobarbituric acid reactive substances (TBARS), antioxidant content and total polyphenols at 0, 15, 30, 60, 90 and 120 days for both MF and MC.The MC sample had pH 7.0, 31.78 mg N-BVT / 100 g sample, 2.02 mg N-TMA / 100 g sample, higher values when compared to the MF sample that presented a pH of 6.79, 21.67 mg of N-TVB / 100 g of sample and 1.33 N-TMA / 100 g of sample, in the period of 120 days, indicating that the addition of cashew fiber helps to maintain the freshness and stability of the medallions during frozen storage.It was also performed an instrumental texture analysis of the medallions, in which the MF sample presented a fraturability force of 8198 Kgf, hardness of 262381 N and a gumminess of 21824 g when compared to MC sample, which presented a fraturability force of 7809 Kgf, hardness of 80035 N and gumminess of 9387, revealing that the addition of fibers in the medallions significantly influence the texture of the product. However, the addition of cashew fiber in the medallions did not influence the chewiness of the product, since the samples did not differ significantly between them, presenting values of 17148 and 20404 for MC and MF, respectively. This higher hardness of the MF formulation also did not affect the sensory acceptability of the product, once the formulation was in the acceptance zone of the hedonic scale. Therefore, the MF formulation is promising for the consumer market.